Development of a Measure of Calculative Mindset (CM): Establishing a Nomological Net and Predictive Utility of the CM Measure. Issue 4 (August 2022) - Kim, Joongseo; Jawahar, I. M.; Steinheider, Brigitte; Stone, Thomas; Ferrell, Brandon
A calculative mindset (CM) describes the tendency to analyze and convert qualitative social values into numeric or monetary metrics and is a predisposition that shapes behaviors and actions of the employee. CM has been manipulated in experimental studies, but it has not been investigated in field research due to the absence of a scale to measure CM. In study 1, we followed Hinkin's scale development protocol to conceptualize, develop, and validate a measure of CM to facilirate research in organizational contexts. In Study 2, we examined the relationship between CM and measures of performance, counterproductive work behavior (CWB), organizational citizenship behaviors (OCB), and in role-performance (IRP). Results from hierarchical regression analyses indicate that CM is related to these performance outcomes and explains incremental variance over established measures of the Five-Factor Model of personality. Implications for personality research, selection of human resources, and facilitation of an ethical workplace are discussed.